THE USE OF POETIC QUOTATIONS IN TEACHING NAHWU RULES THROUGH KITĀBI AL-ḤIWĀR FĪ SHARḤ AL-ĀJURRŪMIYYAH: توظيف الشواهد الشعرية لتعليم القواعد النحوية من خلال كتاب الحوار في شرح الآجُرُّومية - Ahyarudin, Ahyarudin; Solihati, Septia (Dirasa Islamiyya: Journal of Islamic Studies, 2025)
This study aims to review the poems cited in the book Al-Hiwār fī Sharḥ al-Ājurrūmiyyah and to analyze how they are used in teaching grammatical rules, as well as to identify the poetic evidences used in teaching these rules. This is library-based research that adopts a qualitative approach, using the descriptive research method. The study addresses various examples that highlight how poetry is used in different grammatical topics such as bāb al-kalām (the chapter of speech), markers of nouns, markers of past tense verbs, signs of particles, subjunctive particles for the present tense, and other grammatical topics. Among the prominent poets cited are Al-Mutanabbī, Ḥassān ibn Thābit, and Abū al-Aswad al-Duʾalī. Their poetry played a role in explaining rules and clarifying grammatical meanings through practical examples. Based on this, the study demonstrates the importance of poetry in facilitating the understanding of grammatical rules by linking theory with practical application, which contributes to enhancing students’ comprehension and reinforcing grammatical concepts in their memory.